ISTIKHDAM USLIB AL-RU'IS AL-MURAQAMAH LI TARQIYAH AL-TAFA'UL AL-SHAFFIZ FIZ TADRIS AL-MUFRADAT - Kusuma, Handoyo; Nawawi, Mukhshon (Arabi : Journal of Arabic Studies, 2018)
This research aimed to find an increase in class interaction using the technique Numbered Head Together (NHT) on learning vocabulary. This type of research was a classroom action research by combining classroom interaction categorization according to Flander as an indicator of improvement. The object of this research was the 7th grade students of MTs Al-ihsan Pamulang academic year 2016-2017. Primary data were obtained through observation instruments and interviews as a form of triangulation. The results of this study indicated an increase in class interaction after going through two cycles, the results in the first cycle had not reached the success the success rate with the percentage of 58% while the second cycle reached 72% with an indication of an increase of 14%.